Abelmoschus rhodopentalus var. binhsonensis: A New Variety of Abelmoschus rhodopentalus in Quang Ngai Province, Vietnam Based on Morphological and DNA Barcode Analyses - Nguyen, Minh Ly; Le, Huynh Thi Diem Suong; Mai, Xuan Cuong; Ba, Duy Vo; Trinh, Dang Mau; Vo, Van Minh (Hue University Journal of Science: Natural Science, 2025)
In this study, we identified Nghia Sam found in Quang Ngai province by morphological and DNA barcode analyses including matK, trnL-F IGS, and ITS. The results showed that Nghia Sam possessed morphological characters of Abelmoschus rhodopentalus such as linear epicalyx (<9), free, persistent; tuberous root; short-stemmed shrub; pink flowers; capsule hairy, and apically dehiscent. In addition, Nghia Sam differed from A. rhodopentalus var. rhodopentalus in having unbranched tuberous roots, branches spreading close to the ground, and pink-spotted flowers. Phylogenetic analysis confirmed that Nghia Sam belongs to the same clade with A. rhodopentalus. Based on current taxonomic keys, Nghia Sam is proposed as a new variety: A. rhodopentalus var. binhsonensis. These findings contribute to clarifying the classification and conservation value of this rare native genetic resource. <!--a=1-->